Negotiating in Silence: Experiences with Parental Leave in Academia - Weststar, Johanna (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
SummaryThis paper presents a case study of pregnancy/parental leave arrangements among faculty members at a mid-sized Canadian university. Pregnancy/parental leaves and associated benefits are often taken for granted, particularly among unionized employees in Canada; however, this research shows that continued vigilance is required to maintain the standard and equity of these rights. The data consist of self-report accounts of faculty experiences in making leave arrangements over the period 2000-2010.The results show inequity in leave arrangements across faculties, across and within departments and for individuals who had more than one leave. Much of this inequity stemmed from individualized “creative” negotiations and problem-solving when the leave was scheduled to begin or end in the middle of an academic term. Many of these solutions penalized faculty members for unassigned teaching duties. Faculty members were requested or felt personally obligated to “cover-off” the teaching time before or after their leave by teaching course overloads, using course releases earned through external research grants, condensing courses, or beginning and/or ending the leave earlier than required.This research has implications for unions who must maintain vigilance and relevance in professional environments where individual negotiation takes place and union consciousness is lower. It also emphasizes the burden placed on parents when the bearing and rearing of children is framed as an individual right rather than an issue of social reproduction. As a result of their “choice” to have a baby and take an associated leave of absence, faculty members can experience guilt, fear and anxiety related to their professional and collegial status. Due to these emotions, and faced with a silent collective agreement, faculty members can accommodate the needs of the university to their own detriment. The paper concludes with recommendations for how faculty unions can better protect pregnancy and parental leave rights through improved formal language in policy documents or collective agreements.